Pemberdayaan Sumber Daya Lokal Dengan Pemanfaatan Limbah Kulit Kopi Robusta (Coffea canephora) Sebagai Biobriket di Desa Tanah Wulan Kabupaten Bondowoso - Purimahua, Amanda Augre Maharani; Hidayat, Debby Aurellia; Dihayat, Icha Shofia; Herdianto, Dimas Nur; Asshofy , Muhammad Agil; Khotimah, Husnul; Lumbantoruan, Sri Lestari; Firmansyah, Muhammad Sahrul; Pravitasiwi, Nanda Tricya Julia; Ramadana, Ifan; Uzinuzulla, Yunita Virda; Palupi, Bekti; Fachri, Boy Arief; Rahmawati, Istiqomah (Universitas Jayabaya, 2024)
Chemical Engineering Mengabdi 2023 is a manifestation of community service contained in one of the tridharma of higher education. Chemical Engineering Mengabdi 2023 activities are a means of transferring knowledge and technology from academics to the community. In the implementation of this activity, Chemical Engineering students of Jember University are expected to help the community overcome the problem of robusta coffee skin waste, and can empower the economy of Tanah Wulan Village residents by providing knowledge about the utilization of local resources and the utilization of coffee skin waste into briquette products with high economic value. The implementation of the service is divided into two, namely socialization and practice of making biobriquettes. Socialization activities were carried out to convey material on processing coffee skin waste into briquettes. Furthermore, the practice of making biobriquettes is carried out using the pyrolysis method. In this service activity, an environmentally friendly biobriquette product was obtained, which has consistent heat efficiency, and an economical price.